2002
DOI: 10.1021/ac020025b
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput, High-Sensitivity Genetic Mutation Detection by Tandem Single-Strand Conformation Polymorphism/Heteroduplex Analysis Capillary Array Electrophoresis

Abstract: We present the first optimization of linear polyacrylamide (LPA)-based DNA separation matrixes for an automated tandem microchannel single-strand conformation polymorphism (SSCP)/heteroduplex analysis (HA) method, implemented in capillary arrays dynamically coated with poly(N-hydroxyethylacrylamide) (polyDuramide). An optimized protocol for sample preparation allowed both SSCP and HA species to be produced in one step in a single tube and distinguished in a single electrophoretic analysis. A simple, two-color … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(96 citation statements)
references
References 29 publications
4
91
0
1
Order By: Relevance
“…With the increase of LPA concentrations, the resolution of ssDNA fragments was improved and all four peaks of the ssDNA conformers presented in the heterozygous sample were separated completely at 4% LPA. The small peaks clustered around the peaks of the ssDNA conformers probably represent primer-ssDNA constructs [24]. At 6% LPA, the resolution of ssDNA fragments was improved slightly but a longer electrophoresis time was required.…”
Section: Resultsmentioning
confidence: 99%
“…With the increase of LPA concentrations, the resolution of ssDNA fragments was improved and all four peaks of the ssDNA conformers presented in the heterozygous sample were separated completely at 4% LPA. The small peaks clustered around the peaks of the ssDNA conformers probably represent primer-ssDNA constructs [24]. At 6% LPA, the resolution of ssDNA fragments was improved slightly but a longer electrophoresis time was required.…”
Section: Resultsmentioning
confidence: 99%
“…However, tandem SSCP/HA through the snapcooling procedure produced similar results with the gradually cooling procedure. 19 The use of 10 mM Tris-HCl (PH 8.6) buffer for sample preparation provided high sensitivity and satisfactory results. Figure 4 shows the results of SSCP/HA of the P53 gene exon 7 of a mutant sample with homemade LPA.…”
Section: Establishment Of the Tandem Lif-ce-sscp/ha Methodsmentioning
confidence: 99%
“…90% [5]). By combining these two techniques (e.g., as in the capillary-based work of [6]) it has been reported that sensitivities of 100% can be achieved.…”
Section: General Aspectsmentioning
confidence: 99%
“…Significant strides have been made in developing microchip-based mutation detection using SSCP [6,20], HA [21,22] as well as restriction enzyme processing (e.g.,…”
Section: Microchip-based Mutation Detectionmentioning
confidence: 99%